The warm winter paradox in the Pliocene northern high latitudes - J. C. Tindall; A. M. Haywood; U. Salzmann; A. M. Dolan; T. Fletcher (Climate of the Past, 2022)
Reconciling palaeodata with model simulations of the Pliocene climate is essential for understanding a world with atmospheric CO2 concentration near 400 ppmv (parts per million by volume). Both models and data indicate an amplified warming of the high latitudes during the Pliocene; however, terrestrial data suggest that Pliocene northern high-latitude temperatures were much higher than can be simulated by models.